Analisis Kepemimpinan Para Pemimpin Organisasi Kemahasiswaan di Universitas Negeri Medan - Hapni Laila Siregar; Farhan Farhan; Irvan Affandi; Isna Firdasari Ajwa; Riris Amigo Simatupang; Rizky Ramadhan (CV. ULIL ALBAB CORP, 2024)
In the context of the development of Student organizations, leadership plays an important role in determining the direction, quality, and success of an organization. Leadership is defined as something that influences others in order to realize the goals of the